Coexisting Lung Cancer and Pulmonary Tuberculosis: A Comprehensive Review From Incidence to Management - Wendi Zhou; Hongxu Lu; Jiamin Lin; Jialou Zhu; Jizhen Liang; Yalin Xie; Jinxing Hu; Ning Su (Cancer Reports)
ABSTRACT Background Globally, infections account for 10% of new cancer cases, and cancer can compromise the immune system, increasing the risk of infections. With advances in cancer treatment, widespread use of immunotherapy, and prolonged survival of cancer patients, the coexistence of tuberculosis (TB) and cancer is becoming increasingly common in clinical settings. Aim This review aims to explore the interaction between tuberculosis (TB) and tumors, particularly lung cancer (LC), and to identify appropriate clinical management approaches. Results LC patients with a history of TB have higher adjusted risk ratios for both all‐cause and cancer‐specific 3‐year mortality compared to those without a history of TB. TB may elevate the risk of developing tumors through mechanisms such as chronic inflammation, altered immune responses, and DNA damage. Conversely, cancer patients, whether due to the disease itself or immune dysfunction caused by anti‐tumor treatments, may be more susceptible to TB. The coexistence of TB and tumors presents significant challenges in clinical management, making the development of treatment strategies and quality‐of‐life improvements crucial. Conclusion There is a close relationship between TB and cancer, with TB potentially serving as a risk factor for cancer, and cancer influencing susceptibility to TB. Effective clinical management is essential to enhance treatment strategies and improve the quality of life for patients with both TB and cancer.